Agent-based modeling of construction firms' organizational behavior in public tenders - Valeriya Gladkikh; Aleksandr Alekseev (Journal of Risk and Financial Management, 2023)
A key problem of construction firms' management and economy is organization of effective participation in public tenders. The direct executor, who determines the price of the contract, may be interested in obtaining as many contracts as possible. It means that his strategic behavior in tender may be to undervalue each individual offer. At the same time, such a strategy can be a source of risk of project loss because the actual costs may be lower than the price of the contract won. The management of the construction organization is not interested in this. On the other hand, overpricing strategy may lead to a reduction in the number of contracts won, which may not seem effective either for the head or for the executor of such an organization. The article discusses whether the profits of a construction firm can increase by using a more precise method of calculating the estimated cost. The second question is-which staff of a construction firm will benefit from using such methods? The aim of this work is to test these hypotheses with the instrumentality of agent-based modeling. Profit values of construction firms were obtained by the computer simulation of the construction firms' strategic behavior in public tenders. Results of 1500 computer experiments are presented as a decision tree. It can be seen that when using a more precise method, construction firms win tenders almost two times less often. However, they incur losses many times less than with an inaccurate method. If a construction firm made a profit from the contracts won, the profit margin was almost always greater when using the more precise method. Moreover, the results of game-theoretic modeling are given. Values of the objective functions of the executor and head of the construction firm were obtained, taking into account the reward for contracts won and penalty for miscalculating the cost of work. It has been proved that using more precise methods for calculating the estimated cost is beneficial to both the head and the executor. It can be concluded that both hypotheses were confirmed and a precise method for calculating the cost increases the efficiency of a construction firm.
Keywords: 650; agent-based modeling; computer simulation; construction firms; multi-agent system; organizational behavior; tenders